The Italian General Election of 2008
XV, 266 p. 13 illus.
Keywords: A lively account of the general election of 2008 and of its profound significance for Italy and beyond. It gets to grips with the complexities of Italian politics in an exceptionally clear way. Covering the background to the election, the campaign, the parties, voting and the outcome, it is comprehensive in approach and tells a fascinating 'story'.